Thermal, physical, structural, thermomechanical features and single gas permeation comparison of fluorine, phenyl phosphine oxide-based copolyimides with poly(dimethylsiloxane) - KAYAMAN APOHAN, NİLHAN; KARATAŞ, SEVİM (SPRINGER, 2017)
In this study, a series of copolyimide have been obtained, using a newly synthesized monomer named bis-(3-aminophenoxy-3-trifluoromethyl-4-phenyl)phenylphosphine oxide (m-BA6FPPO), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), 4,4'-oxydianiline (ODA) and poly(dimethylsiloxane) (PDMS, amine terminated, M (n) = 2500 g/mol). Homogeneous cavity distribution and homogeneous porosity appeared for the copolyimide containing 1.5 wt% of poly(dimethylsiloxane). The tensile strength and modulus of the materials containing 1.5 wt% of poly(dimethylsiloxane) had the highest values among others. The decomposition temperatures increased with increase of PDMS content. In general, hybrid materials were transparent. Storage moduli of 1.5 and 2 wt% of silicone containing materials were greater than those of others. The optimum results for the single gas permeability were achieved at 1 bar for the materials containing 1.5 and 2 wt% poly(dimethylsiloxane). The volume fraction of silicone was determined from thermomechanical analysis at a certain temperature for each sample. The best correlation between volume fraction of silicone and selectivities was obtained for CH4/CO2, CH4/N-2, CO2/O-2, CO2/N-2 and CH4/O-2. Bis-(3-aminophenoxy-3-trifluoromethyl-4-phenyl)phenylphosphine oxide ingredient in the same amounted silicone containing materials decreased the permeabilities of gases such as CO2, CH4, H-2, while increased O-2 permeability at 1 bar.
Keywords: Fluoropolymers; Polyimides; Poly(dimethylsiloxane); Single gas permeation; POLYMERIC MEMBRANES; SEPARATION; PERMEABILITY; POLYIMIDES; SILOXANE